2012
DOI: 10.4103/1119-3077.104505
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of respiratory symptoms and lung function among textile workers at Kano Textile Mills, Kano, Nigeria

Abstract: Respiratory symptoms were more prevalent among workers in most dusty sections of the factory. Use of protective mask should be enforced. Workers in the spinning and weaving sections of the company compared with workers in other sections had the lowest lung function indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
21
4
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 8 publications
9
21
4
7
Order By: Relevance
“…This finding is in agreement with a study done in Nigeria, which reported spinning section had the highest frequency of symptoms, followed by weaving (Nagoda et al, 2012). Report by OSEJI et al (2006) revealed a higher prevalence of respiratory symptoms among spinners compared to workers in other sections (OSEJI et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This finding is in agreement with a study done in Nigeria, which reported spinning section had the highest frequency of symptoms, followed by weaving (Nagoda et al, 2012). Report by OSEJI et al (2006) revealed a higher prevalence of respiratory symptoms among spinners compared to workers in other sections (OSEJI et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in line with the work of Nagoda et al (2012) in Kano textile workers, Nigeria in which the mean values of PEFR, FVC, and FEV 1 of exposed group were lower than those of the controls.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There was decreased level of PEFR was observed in the exposed group of textile mill workers compared to non-exposed workers. Moreover, a Nigerian based study also reported a significant decrease in FVC, FEV 1 , and PEFR in exposed workers from a textile mill when compared to unexposed group similar to this study [21]. An increased BMI also plays a significant role in increasing health-related issues.…”
Section: Discussionsupporting
confidence: 85%